Al-Tarbiyah Al-Syahshiyah fi Indonesia (Diraasah min Al-Ithaar Al-Falsafi, wa Al-Qaanuun, wa Al-Tanfiidz, wa Al-Isykaaliyaat) - Sembodo Ardi Widodo (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2015)
This article aims to describe the phenomena of character education in Indonesia. The study covers aspects of the philosophical outline about the importance of character education, the rudiments of law used as the basis, the implementation of character education at schools, and problems appeared in the field. Many cases such as corruption, juvenile delinquency, drugs miss-use, social conflict, and environmental damage occurred in Indonesia are among important factors of the implementation of character education. In this case, the government already set up the 18 character values that implanted through education, namely religiousness, honesty, tolerance, discipline, hard working, creativity, independence, democracy, curiosity, nationalism, patriotism, achievement, friendship and communication, peace-loving, reading, environmental care, social care, and accountability. Nonetheless, there are still many obstacles in the implementation of character education in the field. Those problems are analyzed comprehensively in this paper.